Resin composition for encapsulation
The resin composition with alumina and other inorganic particles addresses the imbalance in thermal conductivity and fluidity, enhancing the stability and performance of electronic components by ensuring homogeneous curing and reducing burrs.
Patent Information
- Application Number
- JP2023117279
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-19
- Publication Date
- 2025-01-30
AI Technical Summary
Existing resin compositions for sealing electronic components struggle to achieve a balanced thermal conductivity and fluidity, leading to issues such as burr formation and uneven curing, which affect the stability and performance of electronic devices.
A resin composition comprising alumina particles and other inorganic particles, with specific particle size distributions and ratios, along with controlled injection parameters, to enhance thermal conductivity and fluidity, ensuring homogeneous curing and reduced burr formation.
The composition achieves a well-balanced thermal conductivity and fluidity, improving the stability and performance of electronic components by preventing burr formation and ensuring uniform filling in narrow gaps.
Smart Images

Figure 2025014591000001 
Figure 2025014591000002 
Figure 2025014591000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an encapsulating resin composition. [Background technology]
[0002] Various technologies have been studied for encapsulating resin compositions for encapsulating electronic elements, etc. One such technology is described in Patent Document 1. Patent Document 1 discloses a composition that contains an epoxy resin, a curing agent, a curing accelerator, an inorganic filler, and at least one of carboxylic acid and its derivatives (excluding esters as carboxylic acid derivatives), and uses fused spherical silica powder (average particle size 30.4 μm) as the inorganic filler. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2019-151852 A Summary of the Invention [Problem to be solved by the invention]
[0004] In the manufacture of electronic components, as described above, a process of encapsulating electronic elements and metal members with an encapsulating resin composition may be performed. In such a process, it is important to appropriately control the flowability when encapsulating electronic elements, etc., from the viewpoint of suppressing the occurrence of encapsulation defects and stably manufacturing electronic components. Specifically, the resin composition may get into fine gaps in a mold, causing burrs in the molded product. Moreover, from the viewpoint of dissipating heat generated in the sealed electronic components to the outside and suppressing malfunction of the electronic components, it is important to increase thermal conductivity. That is, there has been a demand for an encapsulating resin composition that has an excellent balance between thermal conductivity and fluidity when encapsulating electronic elements and the like.
[0005] Meanwhile, when the present inventors have examined the above-mentioned resin composition, it has become clear that there is room for improvement in the balance between thermal conductivity and fluidity.
[0006] In view of the above background, the present invention provides an encapsulating resin composition that achieves a good balance between thermal conductivity and fluidity. [Means for solving the problem]
[0007] As a result of investigations, the present inventors have completed the invention provided below and have solved the above-mentioned problems.
[0008] [1] An inorganic filler; A thermosetting resin; A hardener; An encapsulating resin composition comprising: The inorganic filler contains alumina particles and inorganic particles other than alumina particles, The encapsulating resin composition has an ash content obtained by measuring the ash content of a cured product of the encapsulating resin composition, and when a particle size distribution curve is plotted with the frequency of a volume-based particle size distribution of ash content measured by a laser diffraction scattering measurement method on the vertical axis and the particle size on the horizontal axis, where Xa is the frequency of the peak top of peak A observed in a particle size range of 0.1 to 1.0 μm and Xb is the frequency of the peak top of peak B observed in a particle size range of 1.0 to 12 μm, Xa / Xb is 0.50 or more and 1.00 or less. [2] An inorganic filler; A thermosetting resin; A hardener; An encapsulating resin composition comprising: The inorganic filler contains alumina particles and inorganic particles other than alumina particles, The mold temperature of the above-mentioned encapsulating resin composition was 175°C, and the injection speed was 300 mm 3 Spiral flow S at 175°C / sec, injection speed 180 mm 3and a rectangular viscosity N of the encapsulating resin composition at 100 / s, and an S / N value calculated from the rectangular viscosity N of the encapsulating resin composition at 100 / s is 55 or more and 100 or less. [3] In the encapsulating resin composition according to the above [1] or [2], The particle size at which the cumulative frequency of the volume-based particle size distribution of the above alumina particles is 10% as determined by the laser diffraction scattering measurement method is defined as D 10 Then, D 10 The encapsulating resin composition has a particle size of 0.1 μm or more and 2.0 μm or less. [4] In the encapsulating resin composition according to any one of the above [1] to [3], The particle size at which the cumulative frequency of the volume-based particle size distribution of the above alumina particles is 50% as determined by the laser diffraction scattering measurement method is defined as D 50 Then, D 50 The encapsulating resin composition has a particle size of 5.0 μm or more and 10.0 μm or less. [5] In the encapsulating resin composition according to any one of the above [1] to [4], The particle size at which the cumulative frequency of the volume-based particle size distribution of the above alumina particles is 90% as determined by the laser diffraction scattering measurement method is defined as D 90 Then, D 90 The encapsulating resin composition according to claim 1, wherein the particle size is 5.0 μm or more and 20.0 μm or less. [6] In the encapsulating resin composition according to any one of the above [1] to [5], The encapsulating resin composition, wherein the alumina particles have a sphericity of 0.60 or more and 1.00 or less as measured by a flow type particle image analyzer. [7] In the encapsulating resin composition according to any one of the above [1] to [6], The encapsulating resin composition has a content of the alumina particles of 55% by mass or more and 95% by mass or less based on the total solid content of the encapsulating resin composition. [8] In the encapsulating resin composition according to any one of the above [1] to [7], The encapsulating resin composition, wherein the thermosetting resin comprises an epoxy resin. [9] In the encapsulating resin composition according to the above [8], The epoxy resin is one or more selected from the group consisting of biphenyl-type epoxy resins, bisphenol-type epoxy resins, novolac-type epoxy resins, multifunctional epoxy resins, aralkyl-type epoxy resins, dicyclopentadiene-type epoxy resins, naphthalene-type epoxy resins, xylok-type epoxy resins, triphenylmethane-type epoxy resins, and anthracene-type epoxy resins.
[10] In the encapsulating resin composition according to any one of the above [1] to [9], The encapsulating resin composition has a content of the thermosetting resin of 2% by mass or more and 35% by mass or less based on the total solid content of the encapsulating resin composition.
[11] In the encapsulating resin composition according to any one of the above items [1] to
[10] , The encapsulating resin composition includes one or more curing agents selected from the group consisting of phenol aralkyl type phenolic resins, bisphenol type phenolic resins, novolac type phenolic resins, polyfunctional phenolic resins, dicyclopentadiene type phenolic resins, naphthalene type phenolic resins, xyloc type phenolic resins, anthracene type phenolic resins, and norbornene type phenolic resins.
[12] In the encapsulating resin composition according to any one of the above items [1] to
[11] , The encapsulating resin composition has a content of the curing agent of 2.0% by mass or more and 20% by mass or less based on the total solid content of the encapsulating resin composition. Effect of the Invention
[0009] According to the present invention, there is provided an encapsulating resin composition that achieves a good balance between thermal conductivity and fluidity. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, an embodiment of the present invention will be described in detail based on the embodiment.
[0011] <Sealing resin composition> The encapsulating resin composition of the present embodiment will be described. The encapsulating resin composition of the present embodiment is an encapsulating resin composition including an inorganic filler, a thermosetting resin, and a curing agent, wherein the inorganic filler includes alumina particles and inorganic particles other than alumina particles, and with respect to the ash content obtained by performing an ash content measurement on a cured product of the encapsulating resin composition, when the frequency of a volume-based particle size distribution of the ash content measured by a laser diffraction scattering measurement method is plotted on the vertical axis and the particle size is plotted on the horizontal axis, the frequency Xa of the peak top of peak A observed in a particle size range of 0.1 to 1.0 μm and the frequency Xb of the peak top of peak B observed in a particle size range of 1.0 to 12 μm are taken as Xa / Xb, which is 0.50 or more and 1.00 or less.
[0012] The encapsulating resin composition of the present embodiment includes an inorganic filler, a thermosetting resin, and a curing agent, and the inorganic filler includes alumina particles and inorganic particles other than alumina particles, so that the thermal conductivity is improved and favorable, and the cured product of the encapsulating resin composition is homogeneous, particularly without unevenness in the components of the inorganic filler. Furthermore, since the value of Xa / Xb is within the above numerical range, the fluidity of the encapsulating resin composition becomes moderately favorable, and the filling property into a narrow mold becomes good, and as a result, the thermal conductivity can be improved. In addition, the generation of burrs caused by the encapsulating resin composition entering a very narrow gap in the mold that is not intended to be filled can be suppressed.
[0013] In the encapsulating resin composition of the present embodiment, a particle size distribution curve is created for the ash content obtained by performing ash content measurement on the cured product of the encapsulating resin composition for the alumina particles and inorganic particles other than the alumina particles, and the frequency Xa of the peak top in peak A observed within a particle size range of 0.1 to 1.0 μm and the frequency Xb of the peak top in peak B observed within a particle size range of 1.0 to 12 μm are controlled, thereby realizing a well-balanced thermal conductivity and fluidity. This is considered to be because the packing property in the unit space between the inorganic fillers is optimal in the process of blending the inorganic filler once into the encapsulating resin composition and further curing it. The particle size distribution of the inorganic filler in the raw material and the particle size distribution of the ash obtained by performing ash content measurement on the cured product of the encapsulating resin composition are different, and as a result, it is considered that the value of Xa / Xb obtained from the particle size distribution of the ash content is in the above-mentioned numerical range, thereby realizing a well-balanced thermal conductivity and fluidity. Such an encapsulating resin composition contains alumina particles and inorganic particles other than alumina particles, and can be obtained by appropriately controlling the particle sizes of the alumina particles and the inorganic particles other than alumina particles, and the content ratio of the alumina particles to the inorganic particles other than alumina particles.
[0014] Regarding the ash content obtained by performing ash content measurement on the cured product of the encapsulating resin composition of this embodiment, in a particle size distribution curve with the frequency of the volume-based particle size distribution of the ash content measured by the laser diffraction scattering measurement method on the vertical axis and the particle size on the horizontal axis, when the frequency Xa of the peak top in peak A observed in the particle size range of 0.1 to 1.0 μm and the frequency Xb of the peak top in peak B observed in the particle size range of 1.0 to 12 μm are taken, Xa / Xb is 0.50 or more and 1.00 or less, but the lower limit of Xa / Xb is 0.50 or more, preferably 0.60 or more, more preferably 0.70 or more, even more preferably 0.75 or more, even more preferably 0.80 or more, and even more preferably 0.85 or more. By having Xa / Xb be equal to or more than the above lower limit, the thermal conductivity is further improved, and the unevenness of the components, especially inorganic fillers, in the cured product of the encapsulating resin composition can be suppressed, resulting in a more homogeneous cured product. The upper limit of Xa / Xb in the encapsulating resin composition of the present embodiment is 1.00 or less, preferably 0.95 or less, and more preferably 0.90 or less. By making Xa / Xb equal to or less than the upper limit, the flowability of the encapsulating resin composition can be further improved.
[0015] Here, the "ash content" in the present embodiment refers to a component that remains unburned when the encapsulating resin composition of the present embodiment is burned. Examples of the combustion conditions for burning the encapsulating resin composition of the present embodiment include heating at 700°C for 3 hours using an electric furnace. In addition, in the laser diffraction scattering type measurement method, a commercially available laser diffraction type particle size distribution measuring device can be used, and is not particularly limited. As a commercially available laser diffraction type particle size distribution measuring device, for example, a laser diffraction type particle size distribution measuring device (SALD-7000, manufactured by Shimadzu Corporation) can be used.
[0016] In addition, as another embodiment of the encapsulating resin composition of the present embodiment, the encapsulating resin composition of the present embodiment is an encapsulating resin composition including an inorganic filler, a thermosetting resin, and a curing agent, the inorganic filler including alumina particles and inorganic particles other than alumina particles, and the encapsulating resin composition is injected at a mold temperature of 175° C. and an injection speed of 300 mm 3 Spiral flow S at 175°C / sec, injection speed 180 mm 3 and a rectangular viscosity N of the encapsulating resin composition at 100 / s, and an S / N value calculated from the rectangular viscosity N of the encapsulating resin composition at 100 / s may be 55 or more and 100 or less.
[0017] The encapsulating resin composition of the present embodiment includes an inorganic filler, a thermosetting resin, and a curing agent, and the inorganic filler includes alumina particles and inorganic particles other than alumina particles, so that the thermal conductivity is improved and the composition is suitable. In addition, the cured product of the encapsulating resin composition is homogeneous, with no unevenness in the components of the inorganic filler. Furthermore, the S / N value is within the above range, so that the fluidity of the encapsulating resin composition is appropriately suitable, and the mold filling property is good, which contributes to improving the thermal conductivity. In addition, the generation of burrs caused by the encapsulating resin composition entering a very narrow gap in the mold that is not intended to be filled can be suppressed.
[0018] Such an encapsulating resin composition contains alumina particles and inorganic particles other than alumina particles, and can be obtained by appropriately controlling the particle sizes of the alumina particles and the inorganic particles other than alumina particles, and the content ratio of the alumina particles to the inorganic particles other than alumina particles.
[0019] In the encapsulating resin composition of the present embodiment, the mold temperature of the encapsulating resin composition is 175° C., and the injection speed is 300 mm 3 Spiral flow S at 175°C / sec, injection speed 180 mm 3The value of S / N calculated from the rectangular viscosity N of the encapsulating resin composition at 1000 / s is 55 or more and 100 or less, with the lower limit of S / N being 55 or more, preferably 56 or more, more preferably 57 or more, and even more preferably 58 or more. By having an S / N ratio equal to or more than the lower limit, the thermal conductivity is further improved, and unevenness of the components, particularly of the inorganic filler, in the cured product of the encapsulating resin composition can be suppressed, resulting in a more homogeneous cured product. The upper limit of the S / N is not more than 100, preferably not more than 95, and more preferably not more than 90. By making the S / N not more than the upper limit, the flowability of the encapsulating resin composition can be further improved.
[0020] Hereinafter, each component contained in the encapsulating resin composition of the present embodiment will be described.
[0021] (Inorganic filler) The encapsulating resin composition of the present embodiment includes an inorganic filler. Furthermore, the inorganic filler includes alumina particles and inorganic particles other than alumina particles. In this way, the value of Xa / Xb and the value of S / N can be controlled, and a good balance between thermal conductivity and fluidity can be achieved. In addition, it also has the function of reducing the increase in moisture absorption amount and the decrease in strength associated with the curing of the encapsulating resin composition.
[0022] In the encapsulating resin composition of the present embodiment, the particle size at which the cumulative frequency of the volume-based particle size distribution of the alumina particles measured by the laser diffraction scattering method is 10% is defined as D 10 Then, D 10 is preferably 0.1 μm or more, more preferably 0.2 μm or more, and further preferably 0.3 μm or more. 10 When the ratio is equal to or more than the lower limit, the fluidity during molding becomes favorable, and the generation of burrs caused by the encapsulating resin composition entering a very narrow gap in a mold that is not intended to be filled can be suppressed. In addition, the D of the alumina particles in the encapsulating resin composition of this embodiment 10 is preferably 2.0 μm or less, more preferably 1.7 μm or less, and even more preferably 1.5 μm or less.10 When the amount of the inorganic filler particles is equal to or less than the upper limit, the number of contact points between the inorganic fillers in the encapsulating resin composition increases, and the encapsulating resin composition has more favorable thermal conductivity. In this case, the above-mentioned laser diffraction particle size distribution measuring device can be used as the device used in the laser diffraction scattering measuring method.
[0023] In the encapsulating resin composition of the present embodiment, the particle size at which the cumulative frequency of the volume-based particle size distribution of the alumina particles measured by the laser diffraction scattering method is 50% is defined as D 50 Then, D 50 is 5.0 μm or more, preferably 6.0 μm or more, and more preferably 6.5 μm or more. 50 When the ratio is equal to or more than the lower limit, the flowability during molding becomes favorable, and the generation of burrs caused by the encapsulating resin composition entering a very narrow gap in a mold that is not intended to be filled can be suppressed. In addition, the D of the alumina particles in the encapsulating resin composition of this embodiment 50 is 10.0 μm or less, preferably 9.0 μm or less, more preferably 8.0 μm or less, and further preferably 7.0 μm or less. 50 When the amount of the inorganic filler particles is equal to or less than the upper limit, the number of contact points between the inorganic fillers in the encapsulating resin composition increases, and the encapsulating resin composition has more favorable thermal conductivity. In this case, the above-mentioned laser diffraction particle size distribution measuring device can be used as the device used in the laser diffraction scattering measuring method.
[0024] In the encapsulating resin composition of the present embodiment, the particle size at which the cumulative frequency of the volume-based particle size distribution of the alumina particles measured by the laser diffraction scattering method is 90% is defined as D 90 Then, D 90is preferably 5.0 μm or more, more preferably 6.0 μm or more, even more preferably 7.0 μm or more, even more preferably 8.0 μm or more, even more preferably 9.0 μm or more, even more preferably 10.0 μm or more, even more preferably 11.0 μm or more, even more preferably 12.0 μm or more, even more preferably 13.0 μm or more, even more preferably 14.0 μm or more, even more preferably 15.0 μm or more, even more preferably 16.0 μm or more. 90 When the ratio is equal to or more than the lower limit, the fluidity during molding becomes favorable, and the generation of burrs caused by the encapsulating resin composition entering a very narrow gap in a mold that is not intended to be filled can be suppressed. In addition, the D of the alumina particles in the encapsulating resin composition of this embodiment 90 is preferably 20.0 μm or less, more preferably 19.0 μm or less, even more preferably 18.0 μm or less, and even more preferably 17.0 μm or less. 90 When the amount of the inorganic filler particles is equal to or less than the upper limit, the number of contact points between the inorganic fillers in the encapsulating resin composition increases, and the encapsulating resin composition has more favorable thermal conductivity. In this case, the above-mentioned laser diffraction particle size distribution measuring device can be used as the device used in the laser diffraction scattering measuring method.
[0025] In the encapsulating resin composition of this embodiment, the sphericity of the alumina particles measured by a flow type particle image analyzer is preferably 0.60 to 1.00, more preferably 0.70 to 1.00, even more preferably 0.75 to 1.00, even more preferably 0.80 to 1.00, even more preferably 0.85 to 1.00, and even more preferably 0.90 to 1.00. When the sphericity is in the above-mentioned numerical range, the number of contact points between inorganic fillers in the encapsulating resin composition increases, and the thermal conductivity of the encapsulating resin composition becomes more suitable. In this case, the sphericity can be calculated from the following formula (1) by observing the particle image using a flow type particle image analyzer (Sysmex Corporation, FPIA-3000) and using the area of the observed particle image as S and the perimeter as L. True sphericity = (4πS) 1 / 2 / L...Formula (1)
[0026] The lower limit of the content of the alumina particles in the encapsulating resin composition of this embodiment is preferably 55% by mass or more, more preferably 60% by mass or more, even more preferably 65% by mass or more, and even more preferably 68% by mass or more, based on the total solid content in the encapsulating resin composition. When the content of the inorganic filler is equal to or more than the lower limit, the thermal conductivity of the encapsulating resin composition becomes more suitable. In addition, the increase in moisture absorption amount and the decrease in strength due to curing of the obtained encapsulating resin composition can be reduced. The upper limit of the content of the alumina particles in the encapsulating resin composition of this embodiment is preferably 95 mass % or less, more preferably 93 mass % or less, even more preferably 85 mass % or less, even more preferably 80 mass % or less, even more preferably 75 mass % or less, even more preferably 70 mass % or less, and even more preferably 69 mass % or less, based on the total solid content in the encapsulating resin composition. When the content of the alumina particles is the above upper limit or less, the obtained encapsulating resin composition has good fluidity and good moldability.
[0027] In this embodiment, the total solid content of the encapsulating resin composition refers to the non-volatile content in the encapsulating resin composition, and refers to the remainder excluding volatile components such as water, solvent, etc. In addition, in this embodiment, the content relative to the total solid content in the encapsulating resin composition, in the case where a solvent is included, refers to the content when the total solid content of the resin composition excluding the solvent is taken as 100 mass %.
[0028] Examples of inorganic particles other than alumina particles include fused silica, spherical silica, fused spherical silica, crystalline silica, silicon nitride, aluminum nitride, etc. These inorganic particles other than alumina particles may be used alone or in combination.
[0029] In the encapsulating resin composition of the present embodiment, the particle size at which the cumulative frequency of the volume-based particle size distribution of inorganic particles other than alumina particles is 10% as determined by a laser diffraction scattering measurement method is defined as D 10 Then, D 10is preferably 0.01 μm or more, more preferably 0.05 μm or more, even more preferably 0.10 μm or more, even more preferably 0.20 μm or more, and even more preferably 0.30 μm or more. 10 When the ratio is equal to or more than the lower limit, the fluidity during molding becomes favorable, and the generation of burrs caused by the encapsulating resin composition entering a very narrow gap in a mold that is not intended to be filled can be suppressed. In addition, D of inorganic particles other than alumina particles in the encapsulating resin composition of this embodiment 10 is preferably 20.0 μm or less, more preferably 15.0 μm or less, even more preferably 10.0 μm or less, even more preferably 5.0 μm or less, and even more preferably 3.0 μm or less. 10 When the amount of the inorganic filler particles is equal to or less than the upper limit, the number of contact points between the inorganic fillers in the encapsulating resin composition increases, and the encapsulating resin composition has more favorable thermal conductivity. In this case, the above-mentioned laser diffraction particle size distribution measuring device can be used as the device used in the laser diffraction scattering measuring method.
[0030] In the encapsulating resin composition of this embodiment, the particle size at which the cumulative frequency of the volume-based particle size distribution of inorganic particles other than alumina particles is 50% as determined by a laser diffraction scattering measurement method is defined as D 50 Then, D 50 is preferably 0.01 μm or more, more preferably 0.05 μm or more, even more preferably 0.10 μm or more, even more preferably 0.20 μm or more, even more preferably 0.30 μm or more, even more preferably 0.40 μm or more, even more preferably 0.50 μm or more, and even more preferably 0.60 μm or more. 50 When the ratio is equal to or more than the lower limit, the fluidity during molding becomes favorable, and the generation of burrs caused by the encapsulating resin composition entering a very narrow gap in a mold that is not intended to be filled can be suppressed. Also, D 50is preferably 30.0 μm or less, more preferably 25.0 μm or less, even more preferably 20.0 μm or less, even more preferably 15.0 μm or less, and even more preferably 10.0 μm or less. 50 When the amount of the inorganic filler particles is equal to or less than the upper limit, the number of contact points between the inorganic fillers in the encapsulating resin composition increases, and the encapsulating resin composition has more favorable thermal conductivity. In this case, the above-mentioned laser diffraction particle size distribution measuring device can be used as the device used in the laser diffraction scattering measuring method.
[0031] In the encapsulating resin composition of the present embodiment, the particle size at which the cumulative frequency of the volume-based particle size distribution of inorganic particles other than alumina particles is 90% as determined by a laser diffraction scattering measurement method is defined as D 90 Then, D 90 is preferably 0.1 μm or more, more preferably 0.2 μm or more, even more preferably 0.3 μm or more, even more preferably 0.4 μm or more, even more preferably 0.5 μm or more, even more preferably 0.6 μm or more, even more preferably 0.7 μm or more, even more preferably 0.8 μm or more. 90 When the ratio is equal to or more than the lower limit, the fluidity during molding becomes favorable, and the generation of burrs caused by the encapsulating resin composition entering a very narrow gap in a mold that is not intended to be filled can be suppressed. In addition, D of inorganic particles other than alumina particles in the encapsulating resin composition of this embodiment 90 is preferably 30.0 μm or less, more preferably 25.0 μm or less, even more preferably 20.0 μm or less, and even more preferably 15.0 μm or less. 90 When the amount of the inorganic filler particles is equal to or less than the upper limit, the number of contact points between the inorganic fillers in the encapsulating resin composition increases, and the encapsulating resin composition has more favorable thermal conductivity. In this case, the above-mentioned laser diffraction particle size distribution measuring device can be used as the device used in the laser diffraction scattering measuring method.
[0032] In the encapsulating resin composition of this embodiment, the sphericity of the inorganic particles other than the alumina particles, as measured by a flow type particle image analyzer, is preferably 0.60 to 1.00, more preferably 0.70 to 1.00, even more preferably 0.75 to 1.00, even more preferably 0.80 to 1.00, even more preferably 0.85 to 1.00, and even more preferably 0.90 to 1.00. When the sphericity is in the above-mentioned numerical range, the number of contact points between the inorganic fillers in the encapsulating resin composition is increased, and the thermal conductivity of the encapsulating resin composition becomes more suitable. In this case, the sphericity can be calculated from the following formula (1) by observing the particle image using a flow type particle image analyzer (Sysmex Corporation, FPIA-3000) and using the area of the observed particle image as S and the perimeter as L. True sphericity = (4πS) 1 / 2 / L...Formula (1)
[0033] The lower limit of the content of inorganic particles other than alumina particles in the encapsulating resin composition of this embodiment is preferably 5 mass% or more, more preferably 7.5 mass% or more, even more preferably 10 mass% or more, even more preferably 12.5 mass% or more, even more preferably 15 mass% or more, even more preferably 17.5 mass% or more, and even more preferably 20 mass% or more, based on the total solid content in the encapsulating resin composition. When the content of inorganic particles other than alumina particles is the above lower limit or more, the flowability of the encapsulating resin composition becomes more suitable. In addition, the increase in moisture absorption amount and the decrease in strength due to curing of the obtained encapsulating resin composition can be reduced. The upper limit of the content of inorganic particles other than alumina particles in the encapsulating resin composition of this embodiment is preferably 40 mass % or less, more preferably 35 mass % or less, even more preferably 30 mass % or less, even more preferably 25 mass % or less, and even more preferably 21 mass % or less, based on the total solid content in the encapsulating resin composition. When the content of inorganic particles other than alumina particles is equal to or less than the upper limit, the resulting encapsulating resin composition has good thermal conductivity and good moldability.
[0034] (thermosetting resin) In the encapsulating resin composition of the present embodiment, a conventionally known thermosetting resin can be used as the thermosetting resin. Examples of the thermosetting resin include epoxy resin, polyimide resin, benzoxazine resin, unsaturated polyester resin, phenol resin, melamine resin, silicone resin, cyanate resin, maleimide resin, acrylic resin, phenol derivative, and derivatives of each resin. As these thermosetting resins, monomers, oligomers, and polymers having two or more reactive functional groups in one molecule can be used, and the molecular weight and molecular structure are not particularly limited. Among them, it is preferable to include an epoxy resin in particular from the viewpoint of thermal conductivity and fluidity.
[0035] Examples of epoxy resins that can be used in the present embodiment include known epoxy resins that are generally used in resin compositions.Examples of known epoxy resins include phenol novolac epoxy resins, cresol novolac epoxy resins, and other novolac epoxy resins obtained by epoxidizing novolac resins obtained by condensing or co-condensing phenols such as phenol, cresol, xylenol, resorcin, catechol, bisphenol A, bisphenol F, and / or naphthols such as α-naphthol, β-naphthol, and dihydroxynaphthalene with compounds having an aldehyde group such as formaldehyde, acetaldehyde, propionaldehyde, benzaldehyde, and salicylaldehyde under an acidic catalyst; bisphenol epoxy resins, for example, bisphenol A, bisphenol F, bisphenol S, bisphenol A / D, and other diglycidyl ethers; biphenyl epoxy resins, which are diglycidyl ethers of alkyl-substituted or unsubstituted biphenols; phenol aralkyl epoxy resins and biphenyl aralkyl epoxy resins synthesized from phenols and dimethoxy-para-xylene or bis(methoxymethyl)biphenyl, naphthol aralkyl epoxides, and naphthol aralkyl epoxides. Aralkyl-type epoxy resins such as epoxy resins; aromatic polyfunctional epoxy resins such as polyfunctional epoxy resins having a fluorene skeleton; stilbene-type epoxy resins; hydroquinone-type epoxy resins; glycidyl ester-type epoxy resins obtained by reacting epichlorohydrin with polybasic acids such as phthalic acid and dimer acid; glycidylamine-type epoxy resins obtained by reacting epichlorohydrin with polyamines such as diaminodiphenylmethane and isocyanuric acid; dicyclopentadiene, which is an epoxidized product of a co-condensation resin of a phenol and a dicyclopentadiene; Examples of epoxy resins include cyclopentadiene-type epoxy resins, naphthalene-type epoxy resins, Zylok-type epoxy resins, triphenylmethane-type epoxy resins, anthracene-type epoxy resins, trimethylolpropane-type epoxy resins, terpene-modified epoxy resins, linear aliphatic epoxy resins obtained by oxidizing olefin bonds with peracids such as peracetic acid, polyfunctional epoxy resins, polyfunctional alicyclic epoxy resins, and epoxy resins obtained by modifying these epoxy resins with silicone, acrylonitrile, butadiene, isoprene-based rubber, polyamide-based resins, etc.Among these, from the viewpoints of thermal conductivity and fluidity, it is preferable to contain one or more compounds selected from the group consisting of biphenyl type epoxy resins, bisphenol type epoxy resins, novolac type epoxy resins, multifunctional epoxy resins, aralkyl type epoxy resins, dicyclopentadiene type epoxy resins, naphthalene type epoxy resins, xylok type epoxy resins, triphenylmethane type epoxy resins, and anthracene type epoxy resins. As the epoxy resin, one or a combination of two or more of the above specific examples can be used.
[0036] The lower limit of the content of the thermosetting resin in the encapsulating resin composition is preferably 2% by mass or more, more preferably 3% by mass or more, even more preferably 4% by mass or more, and even more preferably 4.5% by mass or more, based on the total solid content in the encapsulating resin composition. By making the content of the thermosetting resin equal to or more than the above lower limit, the flowability of the encapsulating resin composition can be improved, and the moldability can be improved. On the other hand, the upper limit of the content of the thermosetting resin in the encapsulating resin composition of this embodiment is preferably 35 mass% or less, more preferably 30 mass% or less, even more preferably 25 mass% or less, even more preferably 20 mass% or less, even more preferably 15 mass% or less, even more preferably 13 mass% or less, even more preferably 11 mass% or less, even more preferably 9 mass% or less, and even more preferably 7 mass% or less, based on the total solid content in the encapsulating resin composition. By setting the content of the thermosetting resin to the above upper limit or less, it is possible to improve the high-temperature reliability and reflow resistance of a power device including an encapsulant formed using the encapsulating resin composition.
[0037] In the present embodiment, from the viewpoint of high-temperature reliability, it is preferable that the encapsulating resin composition contains as few ionic impurities as possible, such as Na ions, Cl ions, and S ions.
[0038] (hardening agent) The curing agent that can be used in the present embodiment includes known curing agents that are generally used in encapsulating resin compositions. Known curing agents include, for example, phenol aralkyl type phenolic resins synthesized from phenols and / or naphthols and dimethoxy paraxylene or bis(methoxymethyl) biphenyl; novolac type phenolic resins such as phenol novolac resin, cresol novolac resin, tert-butylphenol novolac resin, nonylphenol novolac resin, and silicon-modified phenol novolac resin; resol type phenolic resin; bisphenol type phenolic resin; polyoxystyrene such as polyparaoxystyrene; multifunctional phenolic resins such as triphenylmethane type phenolic resin and biphenylene skeleton-containing multifunctional phenolic resin; dicyclopentadiene type phenolic resin; naphthalene type phenolic resin; naphthylene ether type phenolic resin; naphthol type phenolic resin; phenol aralkyl type phenolic resin; biphenyl aralkyl type phenolic resin; trihydroxyphenylmethane type phenolic resin; nitrogen-containing phenolic resin; xylok type phenolic resin, anthracene type phenolic resin, and norbornene type phenolic resin. Among these, from the viewpoints of thermal conductivity and fluidity, it is preferable to include one or two types selected from the group consisting of phenol aralkyl type phenolic resins, bisphenol type phenolic resins, novolac type phenolic resins, polyfunctional phenolic resins, dicyclopentadiene type phenolic resins, naphthalene type phenolic resins, xyloc type phenolic resins, anthracene type phenolic resins, and norbornene type phenolic resins, and it is more preferable to include a polyfunctional phenolic resin. These may be used alone or in combination of two or more.
[0039] The lower limit of the content of the curing agent in the encapsulating resin composition of the present embodiment is preferably 2.0 mass% or more, more preferably 2.5 mass% or more, even more preferably 3.0 mass% or more, and even more preferably 3.5 mass% or more, based on the total solid content in the encapsulating resin composition. By making the content of the curing agent equal to or more than the above lower limit, the flowability of the encapsulating resin composition can be improved, and the moldability can be improved. On the other hand, the upper limit of the content of the curing agent is preferably 20 mass % or less, more preferably 15 mass % or less, further preferably 10 mass % or less, and further preferably 5 mass % or less, based on the total solid content in the encapsulating resin composition. By setting the content of the curing agent to the above upper limit or less, it is possible to improve the high temperature reliability and reflow resistance of a power device including an encapsulant formed using the encapsulating resin composition.
[0040] (Other Ingredients) The encapsulating resin composition of the present embodiment may contain the following components in addition to the above components.
[0041] (Cure accelerator) The encapsulating resin composition of the present embodiment preferably further contains a curing accelerator. The curing accelerator has a function of accelerating the reaction between the reactive group of the thermosetting resin and the reactive group of the curing agent, and a conventionally known curing accelerator is used.
[0042] Specific examples of the curing accelerator include phosphorus atom-containing compounds such as organic phosphines, tetra-substituted phosphonium compounds, phosphobetaine compounds, adducts of phosphine compounds and quinone compounds, and adducts of phosphonium compounds and silane compounds; amidines and tertiary amines, such as 1,8-diazabicyclo(5,4,0)undecene-7, benzyldimethylamine, and 2-methylimidazole, as well as nitrogen atom-containing compounds such as quaternary salts of the above amidines and amines, and one or more of these can be used in combination. Among these, phosphorus atom-containing compounds are preferred from the viewpoint of curability, and phosphobetaine compounds and adducts of phosphine compounds and quinone compounds are particularly preferred from the viewpoint of high temperature reliability and fluidity, and phosphorus atom-containing compounds such as tetra-substituted phosphonium compounds and adducts of phosphonium compounds and silane compounds are particularly preferred in terms of mild contamination of the mold during continuous molding.
[0043] Examples of organic phosphines that can be used in the encapsulating resin composition of the present embodiment include primary phosphines such as ethylphosphine and phenylphosphine; secondary phosphines such as dimethylphosphine and diphenylphosphine; and tertiary phosphines such as trimethylphosphine, triethylphosphine, tributylphosphine, and triphenylphosphine.
[0044] Examples of the tetra-substituted phosphonium compound that can be used in the encapsulating resin composition of the present embodiment include compounds represented by the following general formula (1).
[0045] [ka]
[0046] In general formula (1), P represents a phosphorus atom; R1, R2, R3, and R4 each independently represent an aromatic group or an alkyl group; A represents an anion of an aromatic organic acid having at least one functional group selected from a hydroxyl group, a carboxyl group, and a thiol group on an aromatic ring; AH represents an aromatic organic acid having at least one functional group selected from a hydroxyl group, a carboxyl group, and a thiol group on an aromatic ring; x and y are integers of 1 to 3; z is an integer of 0 to 3, and x=y.
[0047] The compound represented by the general formula (1) can be obtained, for example, as follows, but is not limited thereto. First, a tetra-substituted phosphonium halide, an aromatic organic acid, and a base are mixed in an organic solvent and mixed uniformly, and an aromatic organic acid anion is generated in the solution system. Next, water is added to precipitate the compound represented by the general formula (1). In the compound represented by the general formula (1), from the viewpoint of excellent balance between the yield during synthesis and the curing acceleration effect, it is preferable that R1, R2, R3, and R4 bonded to the phosphorus atom are phenyl groups, and AH is a compound having a hydroxyl group in an aromatic ring, that is, a phenolic compound, and A is an anion of the phenolic compound. The phenolic compound includes, in the concept, monocyclic phenol, cresol, catechol, resorcin, condensed polycyclic naphthol, dihydroxynaphthalene, (polycyclic) bisphenol A, bisphenol F, bisphenol S, biphenol, phenylphenol, phenol novolac, etc. having multiple aromatic rings, and among them, a phenolic compound having two hydroxyl groups is preferably used.
[0048] The lower limit of the content of the curing accelerator is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, even more preferably 0.10% by mass or more, even more preferably 0.15% by mass or more, even more preferably 0.20% by mass or more, even more preferably 0.25% by mass or more, even more preferably 0.30% by mass or more, and even more preferably 0.35% by mass or more, based on the total solid content in the encapsulating resin composition. If the lower limit of the content of the curing accelerator is within the above range, the curability and high-temperature reliability of the encapsulating resin composition can be improved. In addition, the upper limit of the content of the curing accelerator is preferably 1.00% by mass or less, more preferably 0.80% by mass or less, even more preferably 0.60% by mass or less, and even more preferably 0.40% by mass or less, based on the total solid content in the encapsulating resin composition. If the upper limit of the content of the curing accelerator is within the above range, the flowability of the encapsulating resin composition can be improved.
[0049] (Silane coupling agent) The encapsulating resin composition of the present embodiment preferably further contains a silane coupling agent. The silane coupling agent has a function of improving adhesion between the thermosetting resin and the inorganic filler when the inorganic filler is contained in the encapsulating resin composition.
[0050] As the silane coupling agent, various types of agents can be used, but it is preferable to use aminosilane, which can improve the flowability of the encapsulating resin composition.
[0051] The aminosilane is not particularly limited, but examples thereof include γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N-β(aminoethyl)γ-aminopropyltrimethoxysilane, N-β(aminoethyl)γ-aminopropylmethyldimethoxysilane, N-phenylγ-aminopropyltriethoxysilane, N-phenylγ-aminopropyltrimethoxysilane, N-β(aminoethyl)γ-aminopropyltriethoxysilane, N-6-(aminohexyl)3-aminopropyltrimethoxysilane, and N-(3-(trimethoxysilyl)propyl)-1,3-benzenedimethanamine.
[0052] The lower limit of the content of the silane coupling agent is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, even more preferably 0.10% by mass or more, even more preferably 0.15% by mass or more, and even more preferably 0.20% by mass or more, based on the total solid content in the encapsulating resin composition. If the lower limit of the content of the silane coupling agent is within the above range, the interface strength between the thermosetting resin and the inorganic filler is not reduced, and high-temperature reliability can be improved. In addition, the upper limit of the content of the silane coupling agent is preferably 1.00% by mass or less, more preferably 0.80% by mass or less, even more preferably 0.60% by mass or less, even more preferably 0.40% by mass or less, even more preferably 0.30% by mass or less, and even more preferably 0.25% by mass or less, based on the total solid content in the encapsulating resin composition. If the upper limit of the content of the silane coupling agent is within the above range, the flowability of the encapsulating resin composition can be improved.
[0053] (Release agent) The encapsulating resin composition of the present embodiment preferably further contains a release agent. Specific examples of the release agent include natural waxes such as carnauba wax, synthetic waxes such as montan acid ester wax and oxidized polyethylene wax, higher fatty acids such as zinc stearate and metal salts thereof, paraffin, etc. One or more of the above specific examples can be blended as the release agent.
[0054] (Low stress agent) The encapsulating resin composition of the present embodiment preferably further contains a stress reducing agent. By containing the stress reducing agent, it is possible to easily control various physical properties of the encapsulating resin composition, such as the linear expansion coefficient and bending strength.
[0055] As the low stress agent, it is preferable to use, for example, one prepared by the following [method]. [method] 66.1 parts by weight of epoxy resin (bisphenol A type epoxy resin) [Javan Epoxy Resins Co., Ltd., jER (registered trademark) YL6810, softening point 45°C, epoxy equivalent 172] is heated to melt at 140°C, and 33.1 parts by weight of organopolysiloxane 1 (organopolysiloxane represented by formula (7)) and 0.8 parts by weight of triphenylphosphine are added and melt-mixed for 30 minutes to obtain a molten reaction product.
[0056] [ka]
[0057] In the above formula (7), the average value of n7 is 7.5.
[0058] Specific examples of other low stress agents include silicone compounds different from the above-mentioned silane coupling agents, such as silicone oil and silicone rubber, polybutadiene compounds, acrylonitrile butadiene copolymer compounds, etc. As the low stress agent, one or a combination of two or more of the above specific examples can be used. As the low stress agent, it is preferable to use, among the above specific examples, for example, the one prepared by the above [method] and a silicone compound other than the silane coupling agent. In addition, it is preferable to use silicone oil as the silicone compound other than the silane coupling agent. Specific examples of the silicone oil include organopolysiloxane. Here, the organopolysiloxane may have functional groups such as epoxy, amino, methoxy, phenyl, carboxyl, hydroxyl, alkyl, vinyl, and mercapto groups introduced into its structure. The functional groups that the organopolysiloxane introduces into its structure are preferably carboxyl, epoxy, and polyether groups.
[0059] An example of a commercially available silicone oil is BY-750 manufactured by Dow Corning Toray Co., Ltd.
[0060] In addition to the other components described above, colorants such as carbon black, red iron oxide, titanium oxide, etc.; fluidity imparting agents such as 2,3-dihydroxynaphthalene, etc.; ion scavengers; inorganic flame retardants such as aluminum hydroxide, magnesium hydroxide, zinc borate, zinc molybdate, phosphazene, etc.; dispersants, etc. may be appropriately blended.
[0061] <Shape> In the present embodiment, the shape of the encapsulating resin composition can be selected depending on the molding method of the encapsulating resin composition, and examples thereof include particulate shapes such as tablets, powders, and granules; and sheets.
[0062] <Manufacturing method> The encapsulating resin composition can be produced, for example, by mixing the above-mentioned components by known means, melt-kneading them with a kneader such as a roll, a kneader or an extruder, cooling, and then pulverizing them. After pulverization, the mixture may be molded to obtain a particulate or sheet-like encapsulating resin composition. For example, the particulate encapsulating resin composition may be molded into a tablet shape. For example, a sheet-like encapsulating resin composition may be obtained by a vacuum extruder. The degree of dispersion, flowability, etc. of the obtained encapsulating resin composition may be appropriately adjusted.
[0063] <Application> The encapsulating resin composition obtained in this embodiment has a high glass transition temperature, and therefore has excellent adhesion to metal members. More specifically, this embodiment makes it possible to improve the adhesion between the encapsulating material and a member made of Ag, Ni, Cu, or an alloy containing at least one of these elements. Furthermore, by using the encapsulating resin composition obtained in this embodiment, a semiconductor device having excellent high-temperature reliability can be obtained.
[0064] In one embodiment of the present invention, the above-mentioned encapsulating resin composition can be used to encapsulate electronic components to produce electronic devices. The electronic devices can be any known electronic devices, but it is preferable to use the composition in a semiconductor package that encapsulates a semiconductor chip. Preferred embodiments of the semiconductor chip include semiconductor chips that use silicon (Si), silicon carbide (SiC), and gallium nitride (GaN).
[0065] The electronic device of the present embodiment can be applied to various known types of semiconductor packages, and can be preferably applied not only to packages applied to memory and logic elements such as dual in-line package (DIP), plastic leaded chip carrier (PLCC), quad flat package (QFP), low profile quad flat package (LQFP), small outline package (SOP), small outline J-lead package (SOJ), thin small outline package (TSOP), thin quad flat package (TQFP), tape carrier package (TCP), ball grid array (BGA), chip size package (CSP), flip chip chip size package (FCCSP), matrix array package ball grid array (MAPBGA), and chip stacked chip size package, but also to packages such as TO-220 that mount power elements such as power transistors.
[0066] Although the encapsulating resin composition of the present invention has been described above, the present invention is not limited thereto. For example, any component capable of exerting a similar function may be added to the encapsulating resin composition of the present invention. EXAMPLES
[0067] The embodiments of the present invention will be described in detail based on Examples and Comparative Examples. It should be noted that the present invention is not limited to the Examples.
[0068] <Examples and Comparative Examples> (Preparation of Encapsulating Resin Composition) For each of the Examples and Comparative Examples, an encapsulating resin composition was prepared as follows. First, the components shown in Table 1 were mixed in a mixer. Next, the resulting mixture was roll-kneaded, cooled, and pulverized to obtain an encapsulating resin composition in the form of a powder or granule. Details of each component in Table 1 are as follows: The content of each component shown in Table 1 indicates the content (mass %) relative to the total solid content in the encapsulating resin composition.
[0069] (raw materials) (Inorganic filler) Inorganic filler 1: Fused spherical silica (TS-6026, manufactured by Micron, D 50 :10μm) Inorganic filler 2: Fused spherical silica (SC-2500-SQ, manufactured by Admatechs Co., Ltd., D 50 =0.6μm) Inorganic filler 3: Alumina particles (AX3-20R, manufactured by Micron, D 10 :2.1μm, D 50 : 3.4μm, D 90 :5.9μm, sphericity: 0.96) Inorganic filler 4: Alumina particles (product number: NA1045W, manufactured by Novoray, D 10 : 1.3μm, D 50 : 6.8μm, D 90 :16.8μm, sphericity: 0.91)
[0070] In the above inorganic filler, D 10 , D 50 and D. 90 was measured by the volumetric particle size distribution by the laser diffraction scattering measurement method using a laser diffraction particle size distribution analyzer (Shimadzu Corporation, SALD-7000). For the above inorganic filler, the sphericity was calculated by observing particle images using a flow type particle image analyzer (FPIA-3000, manufactured by Sysmex Corporation), with the area of the observed particle image being S and the perimeter being L, according to the following formula (1). True sphericity = (4πS)1 / 2 / L...Formula (1)
[0071] (Coloring agent) Colorant 1: Carbon black (ESR-2001, manufactured by Tokai Carbon Co., Ltd.)
[0072] (Silane coupling agent) Silane coupling agent 1: Phenylaminopropyltrimethoxysilane (CF-4083, manufactured by Dow Corning Toray Co., Ltd.)
[0073] (thermosetting resin) Thermosetting resin 1: Multifunctional epoxy resin (YX-4000K, manufactured by Mitsubishi Chemical Corporation) Thermosetting resin 2: Phenol aralkyl type epoxy resin containing biphenylene skeleton (NC3000, manufactured by Nippon Kayaku Co., Ltd.) Thermosetting resin 3: Triphenylmethane type epoxy resin (YL6677, manufactured by Mitsubishi Chemical Corporation)
[0074] (hardening agent) Hardener 1: Biphenylene skeleton-containing polyfunctional phenolic resin (MEH-7851SS, manufactured by Meiwa Kasei Co., Ltd.) Hardener 2: Formaldehyde-modified triphenylmethane phenolic resin (HE910-20, Air Water)
[0075] (Cure accelerator) Curing accelerator 1: a tetra-substituted phosphonium compound represented by the following formula (8) [ka]
[0076] (Release agent) Release agent 1: Montan acid ester wax (Recorb WE-4, Clariant Japan)
[0077] (Ion scavenger) Ion scavenger 1: Hydrotalcite (DHT-4H, manufactured by Kyowa Chemical Industry Co., Ltd.)
[0078] (Low stress agent) Low stress agent 1: Melt reaction product obtained by the following method [method] 66.1 parts by weight of epoxy resin (bisphenol A type epoxy resin) [Javan Epoxy Resins, jER (registered trademark) YL6810, softening point 45°C, epoxy equivalent 172] was heated to melt at 140°C, and 33.1 parts by weight of organopolysiloxane 1 (organopolysiloxane represented by formula (7)) and 0.8 parts by weight of triphenylphosphine were added and melt-mixed for 30 minutes to obtain a molten reaction product.
[0079] [ka]
[0080] In the above formula (7), the average value of n7 is 7.5.
[0081] (Physical property evaluation) The physical properties of the encapsulating resin composition obtained in each example were evaluated by the following methods.
[0082] (Ash particle size distribution) The encapsulating resin composition of each Example and Comparative Example was injected and molded using a low pressure transfer molding machine (KTS-30, manufactured by Kotaki Seiki Co., Ltd.) under the conditions of a mold temperature of 175°C, an injection pressure of 9.8MPa, and a curing time of 120 seconds, to obtain a molded product having a length of 80 mm, a width of 10 mm, and a thickness of 4 mm. The molded product obtained was heat-treated at 175°C for 4 hours as a post-cure to obtain a test piece. The test piece was then heated at 700°C for 3 hours in an electric furnace to combust the resin component. The ash remaining without combustion was measured by a volume-based particle size distribution by a laser diffraction scattering measurement method using a laser diffraction particle size distribution analyzer (SALD-7000, manufactured by Shimadzu Corporation). The measurement results were plotted as a particle size distribution curve with the frequency of the volumetric particle size distribution of the ash measured by the laser diffraction scattering method on the vertical axis and the particle size on the horizontal axis. In this particle size distribution curve, the frequency Xa of the peak top of peak A observed in the particle size range of 0.1 to 1.0 μm, the frequency Xb of the peak top of peak B observed in the particle size range of 1.0 to 12 μm, and the value (Xa / Xb) obtained by dividing the above Xa by the above Xb were calculated.
[0083] (Spiral Flow Gel Time) Using a low-pressure transfer molding machine (Kotaki Seiki Co., Ltd., "KTS-15"), the mold temperature was 175°C, the injection pressure was 6.9MPa, and the injection speed was 300mm for a spiral flow measurement mold conforming to ANSI / ASTM D 3123-72. 3 The encapsulating resin composition of each Example and Comparative Example was injected under conditions of a pressure drop of 1 / sec and a pressure retention time of 120 seconds, and the flow length (cm) was measured and defined as the spiral flow S. The time from the start of injection until the resin composition hardened and no longer flowed was measured and defined as the gel time. The measurement results are shown in Table 1. The spiral flow S is a parameter of fluidity, and the larger the value, the better the fluidity.
[0084] (Rectangular viscosity) A low-pressure transfer molding machine (KOTAKISEIKI Co., Ltd., "KTS-15") was used, with a mold temperature of 175°C and an injection speed of 180 mm. 3 The encapsulating resin composition of each Example and Comparative Example was injected into a rectangular flow path having a width of 15 mm, a thickness of 1 mm, and a length of 170 mm under conditions of 1 / sec, and the change in pressure over time was measured using a pressure sensor embedded 25 mm from the upstream end of the flow path. The minimum pressure (MPa) when the semiconductor encapsulating resin composition was flowing was measured and this was taken as the rectangular viscosity.
[0085] (S / N) The mold temperature of the encapsulating resin composition measured above (spiral flow gel time) was 175°C, and the injection speed was 300 mm 3The spiral flow at 1000 rpm was defined as S, and the mold temperature of the encapsulating resin composition measured above (rectangular viscosity) was 175°C, and the injection speed was 180 mm. 3 The rectangular viscosity of the encapsulating resin composition at 1 / sec was defined as N, and the S / N value was calculated.
[0086] (Flexural strength, flexural modulus) The flexural strength and flexural modulus of the obtained encapsulating resin composition were measured for each Example and Comparative Example. The measurement was performed by using a low pressure transfer molding machine (KTS-30, manufactured by Kotaki Seiki Co., Ltd.) to inject and mold the resin composition under the conditions of a mold temperature of 175°C, an injection pressure of 9.8MPa, and a curing time of 120 seconds, to obtain a molded product having a length of 80 mm, a width of 10 mm, and a thickness of 4 mm. The obtained molded product was heat-treated at 175°C for 4 hours as a post-cure to obtain a test piece, and the flexural strength and flexural modulus were measured at an ambient temperature of 260°C in accordance with JIS K 6911. The measurement results are shown in Table 1.
[0087] (Thermal Conductivity) Using a low pressure transfer molding machine (KTS-30, manufactured by Kotaki Seiki Co., Ltd.), the encapsulating resin compositions obtained in each Example and Comparative Example were injected and molded under conditions of a mold temperature of 175°C, an injection pressure of 9.8 MPa, and a curing time of 120 seconds to mold test pieces measuring 10 mm in length, 10 mm in width, and 1 mm in thickness. These test pieces were post-cured at 175°C for 4 hours, and the thermal diffusivity was measured using a laser flash thermal constant measuring device LFA467 manufactured by NETZCH, and the thermal conductivity (W / m°C) was calculated from the specific heat and specific gravity.
[0088] (Slit burrs) The encapsulating resin composition of each Example and Comparative Example was molded by transfer molding into a mold having a cavity with a height of 5 μm, a width of 4 mm, and a length of 72 mm at an injection pressure of 10 MPa, a mold temperature of 175° C., and a curing time of 120 seconds. The length of the resin composition that penetrated into the cavity was measured with a vernier caliper, and this was taken as the numerical value of the slit burrs, which is an index of fluidity.
[0089] [Table 1]
[0090] In the above examples, by adding alumina particles and inorganic particles other than alumina particles and by making the Xa / Xb value or the S / N value fall within a specific numerical range, it was possible to provide an encapsulating resin composition that achieves a good balance between thermal conductivity and fluidity.
Claims
1. An inorganic filler; A thermosetting resin; A hardener; An encapsulating resin composition comprising: The inorganic filler includes alumina particles and inorganic particles other than alumina particles, The encapsulating resin composition has an ash content obtained by measuring the ash content of a cured product of the encapsulating resin composition, and when a particle size distribution curve is plotted with a volume-based particle size distribution frequency of ash content measured by a laser diffraction scattering measurement method on the vertical axis and particle size on the horizontal axis, where Xa is a frequency of peak tops in peak A observed in a particle size range of 0.1 to 1.0 μm and Xb is a frequency of peak tops in peak B observed in a particle size range of 1.0 to 12 μm, Xa / Xb is 0.50 or more and 1.00 or less.
2. An inorganic filler; A thermosetting resin; A hardener; An encapsulating resin composition comprising: The inorganic filler includes alumina particles and inorganic particles other than alumina particles, The mold temperature of the encapsulating resin composition was 175° C., and the injection speed was 300 mm 3 Spiral flow S at 175°C / sec, injection speed 180 mm 3 and a rectangular viscosity N of the encapsulating resin composition at 100 / s, and an S / N value calculated from the rectangular viscosity N of the encapsulating resin composition at 100 / s is 55 or more and 100 or less.
3. The encapsulating resin composition according to claim 1 or 2, The particle size at which the cumulative frequency of the volume-based particle size distribution of the alumina particles measured by the laser diffraction scattering method is 10% is defined as D 10 When this is done, D 10 The encapsulating resin composition according to claim 1, wherein the particle size is 0.1 μm or more and 2.0 μm or less.
4. The encapsulating resin composition according to claim 1 or 2, The particle size at which the cumulative frequency of the volume-based particle size distribution of the alumina particles measured by the laser diffraction scattering method is 50% is defined as D 50 When this is done, D 50 The encapsulating resin composition according to claim 1, wherein the particle size is 5.0 μm or more and 10.0 μm or less.
5. The encapsulating resin composition according to claim 1 or 2, The particle size at which the cumulative frequency of the volume-based particle size distribution of the alumina particles measured by the laser diffraction scattering method is 90% is defined as D 90 When this is done, D 90 The encapsulating resin composition according to claim 1, wherein the average particle diameter is 5.0 μm or more and 20.0 μm or less.
6. The encapsulating resin composition according to claim 1 or 2, the alumina particles have a sphericity of 0.60 or more and 1.00 or less as measured by a flow type particle image analyzer.
7. The encapsulating resin composition according to claim 1 or 2, The encapsulating resin composition has a content of the alumina particles of 55% by mass or more and 95% by mass or less based on the total solid content of the encapsulating resin composition.
8. The encapsulating resin composition according to claim 1 or 2, The encapsulating resin composition, wherein the thermosetting resin comprises an epoxy resin.
9. The encapsulating resin composition according to claim 8, The epoxy resin is one or more selected from the group consisting of biphenyl type epoxy resins, bisphenol type epoxy resins, novolac type epoxy resins, polyfunctional epoxy resins, aralkyl type epoxy resins, dicyclopentadiene type epoxy resins, naphthalene type epoxy resins, xylok type epoxy resins, triphenylmethane type epoxy resins, and anthracene type epoxy resins.
10. The encapsulating resin composition according to claim 1 or 2, The encapsulating resin composition has a content of the thermosetting resin of 2% by mass or more and 35% by mass or less based on the total solid content of the encapsulating resin composition.
11. The encapsulating resin composition according to claim 1 or 2, The encapsulating resin composition includes one or more curing agents selected from the group consisting of phenol aralkyl type phenolic resins, bisphenol type phenolic resins, novolac type phenolic resins, polyfunctional phenolic resins, dicyclopentadiene type phenolic resins, naphthalene type phenolic resins, xyloc type phenolic resins, anthracene type phenolic resins, and norbornene type phenolic resins.
12. The encapsulating resin composition according to claim 1 or 2, The encapsulating resin composition has a content of the curing agent of 2.0 mass % or more and 20 mass % or less based on the total solid content of the encapsulating resin composition.
Citation Information
Patent Citations
Epoxy resin composition for encapsulating electronic component, and electronic component device
JP2019151852A